(untitled) (Journal of Asian Development Studies, 2024)
This study investigates the impact of digital transformation on firm performance in small and medium enterprises (SMEs), with the mediating role of operational capabilities. Data is collected through a structured questionnaire from managers and employees of SMEs in Islamabad and Rawalpindi. The hypothesised relationship among the variables is validated through PLS-SEM using SmartPLS. The findings revealed that digital transformation has a significant effect on firm performance. Further, it is also revealed that operational capabilities significantly mediate the relationship between digital transformation and firm performance. These findings highlight the importance of operational capabilities and digital transformation for enhancing firm performance, providing valuable insights for managers, leaders, and SMEs. This research advances the existing literature by integrating digital transformation and operational capabilities, offering a novel perspective on their combined effects on SME performance.